Using Coil-Wire Method to Improve Heat Transfer Characteristics in Pipe Flow: A Mini Review Study - Sarmad A. Ali Sciences (Al-Iraqia Journal for Scientific Engineering Research)
The heat exchanger was invented in thermal contact and at different temperatures for the transfer of enthalpy (thermal energy) between two or more liquids or a liquid and solid surface (one medium to another medium). Basic units called heat exchangers are used to extract and recover heat in the industrial process globally. Various applications and devices use the heat exchanger to exchange heat between two media, including cooling towers, car radiators, condensers, evaporators, etc. An improved technique in the field of heat transfer serves as a research task and is classified as an active, passive, and large-scale composite technique. Active methods need an external power source for the input process and do not need an additional power source or power to improve heat transfer. Passive methods are generally used in both numerical and experimental applications to save energy and cost in enhancing heat transfer and friction losses. The inclusion of wire coils, internal threads, and nanofluid comes under passive methods, which are used to improve the heat exchanger's overall performance and thermal efficiency. The current review investigates the enhancement of the heat transfer rate using wire coils as a means of optimization for two types of laminar and turbulent flow. The current work proposal for future studies of the same field is to use two techniques to improve heat transfer, including a wire coil with a hybrid nanofluid to enhance the thermal conductivity coefficient.